Big Hair, Don't Care - Swain-Bates, Crystal; Bair, Megan (Walnut, CA : Goldest Karat Publishing, 2013)
Lola has curly hair which is much bigger than that of other kids at her school, but she tells anyone who listens how much she loves her hair. Designed to boost self-esteem and build confidence, this book is aimed at boys and girls who may need a reminder that it's okay to look different from the other kids at their school.
Keywords: Hairdressing of African Americans -- Juvenile fiction; Self-confidence -- Juvenile fiction; Hairdressing of African Americans -- Fiction; Self-confidence -- Fiction; Picture books for children